2009
DOI: 10.1055/s-0029-1241862
|View full text |Cite
|
Sign up to set email alerts
|

COUP-TFII is Regulated by High Glucose in Endothelial Cells

Abstract: Diabetes mellitus is an important risk factor for cardiovascular diseases. Clinical evidence supports a link between hyperglycemia, endothelial dysfunction, and vascular disorders. However, the precise molecular mechanisms causing endothelial dysfunction in diabetic patients remain unclear. An interesting novel mediator could be chicken ovalbumin upstream promoter-transcription factor II (COUP-TFII), which plays an essential role in glucose metabolism. COUP-TFII is known to be expressed in venous endothelial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
(32 reference statements)
0
7
0
Order By: Relevance
“…Primary cultures of HUVEC were isolated using 0.5% collagenase II solution (Worthington Biochemical Corp., Lakewood NJ, USA) [32], [33], [34]. Isolated HUVEC were cultured on 2% gelatin-coated plates in Medium 199 (Thermo Fisher Scientific, Waltham, MA, USA), supplemented with 10% fetal calf serum (Biochrom, Berlin, Germany), 0.5% self-isolated retina calf eye growth supplement [35], 100,000 U/l penicillin (Thermo Fisher Scientific, Waltham, MA, USA), 100 mg/l streptomycin (Thermo Fisher Scientific, Waltham, MA, USA) and 250 mg/l Fungizone (Thermo Fisher Scientific, Waltham, MA, USA). HUVEC were freshly isolated on a weekly manner and only used for experiments up to passage 2.…”
Section: Methodsmentioning
confidence: 99%
“…Primary cultures of HUVEC were isolated using 0.5% collagenase II solution (Worthington Biochemical Corp., Lakewood NJ, USA) [32], [33], [34]. Isolated HUVEC were cultured on 2% gelatin-coated plates in Medium 199 (Thermo Fisher Scientific, Waltham, MA, USA), supplemented with 10% fetal calf serum (Biochrom, Berlin, Germany), 0.5% self-isolated retina calf eye growth supplement [35], 100,000 U/l penicillin (Thermo Fisher Scientific, Waltham, MA, USA), 100 mg/l streptomycin (Thermo Fisher Scientific, Waltham, MA, USA) and 250 mg/l Fungizone (Thermo Fisher Scientific, Waltham, MA, USA). HUVEC were freshly isolated on a weekly manner and only used for experiments up to passage 2.…”
Section: Methodsmentioning
confidence: 99%
“…Surgery and transplantation are also associated with hypoxia, which is kept as short as possible. The choice of the period of the short-term hypoxia was based on studies already conducted by other groups, such as Brunssen et al (short-term hypoxia 60-240 min) and Wein et al (short-term hypoxia 30-60 min) [68,69].…”
Section: Hypoxia and Normoxia Conditionsmentioning
confidence: 99%
“…Rao et al investigated the association between glucose levels and ankle range of motion and stiffness and found that passive ankle stiffness and reduced dorsiflexion range of motion were increased in individuals with DM [20]. Research has also revealed that elevated glucose may increase oxidative stress, which induces endothelial dysfunction and impairs venoconstriction responsiveness [21,22], and that hypertriglyceridaemia could exacerbate endothelial inflammation and induce endothelial dysfunction [23,24]. These factors may explain why DM is the most important risk factor, among all the components of MS, for early CVD in our study and why the blood glucose and TG control status is associated with venous function of the lower extremities in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%